How to convert a 3D printer to a personal automated liquid handler for life science workflows - Dulguunnaran Naranbat; Benjamin Phelps; John Murphy; Anubhav Tripathi (SLAS Technology)
Automated liquid handlers are fundamental in modern life science laboratories, yet their high costs and large footprints often limit accessibility for smaller labs. This study presents an innovative approach to decentralizing a liquid handling system by converting a low-cost 3D printer into a customizable and accurate liquid handler. The Personal Automated Liquid Handler (PALH) system, costing ∼$400, incorporates a single-channel pipet, custom 3D-printed components, and open-source software for personalized workflows, allowing researchers to build and modify the system for specific experimental needs. The PALH system was evaluated through common life science assays, including preparing real-time PCR samples, end-point PCR with novel pipet-based downstream purification, and genomic DNA extraction from peripheral whole blood. In real-time PCR experiments targeting the YWHAZ gene, the PALH system demonstrated comparable performance to manual preparation across DNA quantities (1 pg to 100 ng). For end-point PCR, the PALH successfully amplified and purified 204 bp and 406 bp amplicons from a pUC19 vector, yielding concentrations similar to manual methods (5.43 ± 0.85 ng/µL vs. 2.10 ± 0.16 ng/µL for 204 bp; 3.74 ± 2.13 ng/µL vs. 1.51 ± 0.15 ng/µL for 406 bp, respectively). In genomic DNA extraction from whole blood, the PALH system achieved comparable DNA yields to manual extraction (49.52 ± 3.13 ng/µL vs. 48.62 ± 5.9 ng/µL), although at higher purity (260/280 ratio of 1.83 ± 0.07 vs. 1.92 ± 0.03), although both are at acceptable ranges. The open-source nature of the PALH system hopefully encourages further community-driven improvements and protocol sharing, fostering innovation and collaboration within the scientific community. As laboratory automation advances, the PALH system could be crucial in democratizing access to high-quality automated liquid handling, particularly in resource-limited settings.